The Chester Beatty Biblical Papyri at Ninety Literature, Papyrology, Ethics - Allen, Garrick Vernon; Rodenbiker, Kelsie Gayle; Royle, Anthony Philip; Unkel, Jill; Gad, Usama Ali Mohamed (Manuscripta Biblica, 2023)
This book engages the Chester Beatty Biblical Papyri, one of the most important collections of early manuscripts of Jewish scripture and the New Testament, by placing them within larger conversations relating to ancient literature and its interpretation, papyrology, and the ethics of collecting and scholarship. Ninety years after Beatty acquired these manuscripts, their value for scholarship and culture remains largely unexplored.